The role of reciprocation in social network formation, with an application to blogging - Alexia Gaudeul; Caterina Giannetti (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
This paper deals with the role of reciprocation in the formation of individuals' social networks. We follow the activity of a panel of bloggers over more than a year and investigate the extent to which initiating a relation brings about its reciprocation. We adapt a standard capital investment model to study how reciprocation affects the build-up of the individual social capital of bloggers, as measured by their links and interactions with others. This allows us to measure the role of content production and relationship building in the dynamics of online social networks and to distinguish between the social networking and media aspects of blogging.
Keywords: C33; D85; L82; 330; Blogs; Friendship; LiveJournal; Reciprocation; Social Capital; Social Networks; Virtuelle Gemeinschaft; Austauschtheorie (Soziologie); Online-Netzwerk; Social Capital